Kekuatan Genggaman Tangan pada Dewasa Muda - Tiasti, Jania; Setiorini, Anggi; Nareswari, Shinta; Sangging, Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2025)
Handgrip strength (HGS) is an important indicator that reflects both musculoskeletal health and overall well-being. Hand grip strength is widely applied in research and clinical practice because its measurement is simple, reliable, and able to represent overall muscle strength. The assessment of HGS is conducted using a handgrip dynamometer, which operates based on specific principles. However, the limited literature on normative data for young adult populations hinders the interpretation of handgrip performance in this age group. One normative study reported that in healthy young adults, the average HGS reached 36.32 kg in men and 22.96 kg in women. These values may vary depending on ethnicity, level of physical activity, and lifestyle habits. Factors influencing HGS include body composition, anthropometric characteristics, sex, age, nutritional status, and physical fitness. Physiologically, men tend to have higher HGS than women due to differences in muscle mass, hormonal levels, and muscle fiber distribution. The decline of HGS with increasing age is closely related to sarcopenia, a condition characterized by reduced muscle strength, mass, and function associated with aging. Therefore, maintaining handgrip strength from an early age is crucial to support daily activities, preserve independence in older age, and serve as an indicator of future health risks.